Infundibulocystic basal cell carcinoma: dermoscopic findings and histologic correlation - Roldán-Marín, Rodrigo (Derm101.com, 2014)
Infundibulocystic basal cell carcinoma is a rare variant. It was first described in 1987 and proposed as a new basal cell carcinoma (BCC) subtype by Ackerman and Walsh in 1990. Dermoscopy is a noninvasive diagnostic technique that allows prompt identification of many types of BCC. However, dermoscopic findings for the infundibulocystic variant have not been reported. In our patient the dermoscopic findings were maple leaf-like areas in the periphery of the tumor, multiple scattered blue-gray dots and globules, short, fine telangiectasia and chrysalis or white-shiny streaks. All these structures had an underlying anatomopathological correlation. CONCLUSION: According to our case report, dermoscopy findings may aid to clearly diagnose this unusual BCC variant with proper histopathological correlation.